Społeczna odpowiedzialność biznesu gwarancją sukcesu przedsiębiorstwa: Corporate Ssocial Responsibility - the guarantee of an enterprise success - Wykowski, Adam (Management and Administration Journal, 2021)
The purpose of this paper is to present corporate social responsibility as one of the key factors in the success of an organization and a source of sustainable enterprise value.The author attempted to identify the relationship between economic and social efficiency and pointed to the recognition and understanding of CSR in economics and management sciences. Also, the nature and importance of social and economic efficiency in the organization, and the effectiveness of the selected approach and its dimensions were shown, as well as environmental responsibility within the meaning of the environment protection, but not only. Ecological aspect of social responsibility arises from the fact that the management of modern enterprise must consider ethics as a very important factor from a social point of view.